The Impact of the Complexity of the Tax System on the Tax Compliance Behavior of Major Taxpayers in Syria (Latakia University Journal - Economic and Legal Sciences Series, 2023)
The aim of this research is to determine the effect of tax complexity on tax compliance behavior of taxpayers in Syria, specifically large taxpayers.                                           To achieve the goal of the study, a field study was conducted after selecting a sample from a community of senior taxpayers in Syria, which numbered (2,399) taxpayers until the date of preparing the study. The sample was selected using the cluster sampling method. The questionnaire was designed and distributed manually and electronically to (334) taxpayers in the Syrian Arab Republic. And 14 forms were excluded because they were not suitable for statistical analysis due to lack of information and inaccurate answers to some questions, bringing the number of forms that were statistically analyzed to 320 forms. The descriptive analytical approach was used, and data was analyzed using the Statistical Package in Social Sciences (SPSS) program. Extracting descriptive statistics (arithmetic mean, standard deviation), one-sample t-analysis was used to test the research hypotheses, and simple regression analysis: to test the effect of the independent variable on the dependent variable.The results of the research showed that the complexity of the tax system adversely affects the tax compliance behavior of taxpayers in Syria, meaning that the more complex the tax system is, the lower the level of compliance.